Mission schools in Batakland (Indonesia), 1861-1940 - Aritonang, Jan S. (Studies in Christian Mission, 1994)
The expansion of Christianity is often described from the viewpoint of the western missionaries. This book, however, focuses on the large group of indigenous teachers and their pupils at the mission schools in Batakland. These educational activities in fact provided the most important incentive for the birth and growth of the Lutheran Batak Church since 1860. With 3 million members this is the largest protestant church in Indonesia, a Southeast Asian country with 190 million inhabitants, 85% of whom are Muslim. The study is based on archival sources in German, Dutch, Indonesian and Batak, as well as on interviews with local teachers. This is an important case-study about the place of education within the missionary enterprise, the cooperation and conflicts between foreign missionaries and their indigenous helpers, the delicate relation between the Dutch colonial government and a German mission board.